Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1097/mpg.0b013e3182801e43
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thrombotic Events in Hospitalized Children and Adolescents With Inflammatory Bowel Disease

Abstract: Hospitalized children and adolescents with IBD are at increased risk for TE. Conservative methods of TE prevention including hydration, mobilization, or pneumatic devices should be considered in hospitalized patients with IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 53 publications
1
77
2
Order By: Relevance
“…The sites of the TE were the cerebral vessels (54.3%), the vessels in the limbs (26.0%), the abdominal vessels (13.0%), and the vessels in the retina and lungs (6.7%). Nylund et al [29] reported that hospitalized children and adolescents with IBD are at increased risk for TE. Conservative methods such as hydration, mobilization, and pneumatic devices should be considered to prevent TE in hospitalized children with IBD.…”
Section: Discussionmentioning
confidence: 99%
“…The sites of the TE were the cerebral vessels (54.3%), the vessels in the limbs (26.0%), the abdominal vessels (13.0%), and the vessels in the retina and lungs (6.7%). Nylund et al [29] reported that hospitalized children and adolescents with IBD are at increased risk for TE. Conservative methods such as hydration, mobilization, and pneumatic devices should be considered to prevent TE in hospitalized children with IBD.…”
Section: Discussionmentioning
confidence: 99%
“…There appears to be an increased risk of deep venous thrombosis in adolescents and adults with IBD, and appropriate preventive measures, including mechanical pneumatic devices and/or chemical prophylaxis, should be deployed. 56,57 Symptomatic pediatric UC can be well treated surgically with acceptable morbidity and demonstrated excellent long-term outcomes. Contemporary operative management through minimally invasive techniques for all stages of operative care is used at many hospitals with children's surgical expertise.…”
Section: Operative Managementmentioning
confidence: 99%
“…7 In a retrospective cohort study analyzing data from 7 448 292 discharges across 5 nonconsecutive years, the relative risk of a TE in a hospitalized child or adolescent with IBD was 2.36. 8 The etiology of the increased risk of TE in IBD is unclear, although it may be due to increased inflammation leading to a combination of both a prothrombotic and a hypercoagulable state. The decision to initiate prophylaxis of venous thrombosis in children with IBD remains an area of debate.…”
Section: Question Are Patients With CD Predisposed To Coagulopathies?mentioning
confidence: 99%
“…The American College of Chest Physicians recommends pharmacologic prophylaxis, whereas the European Society for Pediatric Gastroenterology, Hepatology, and Nutrition does not recommend prophylactic measures given the lack of evidence of efficacy. 8…”
Section: Question Are Patients With CD Predisposed To Coagulopathies?mentioning
confidence: 99%